PENINGKATAN EKONOMI MELALUI AKUAPONIK PADA KELOMPOK BUDIDAYA IKAN LELE (BIL) DUSUN PASIRDATAR DESA MEKARJAYA KECAMATAN BAREGBEG KABUPATEN CIAMIS - Setiawan, Iwan; Kusniawati, Aini (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2020)
The problems are in this community service were the lack of socialization of the aquaponic system, the lack of knowledge of the aquaponic system in creating double income, community do not understand the implementation of the aquaponic system, The absence of assistance in finding solutions to problems, what is the impact of community service activities on increasing family income. The purpose of community service is to help find solutions in solving problems faced by catfish enlargement cultivation business groups. Mainly related to increasing community economic income through a simple Aquaponic Production Management system. The solution provided is by introducing Mutualism Production Management, namely processing water for catfish enlargement ponds to be used as liquid fertilizer as vegetable nutrition with the aquaponic system. The target is to increase the economy (valued added) through the use of available resources such as catfish excrement as an additional effort in the hope that they can add business units to increase their income apart from the core business of raising catfish. The method used were training and Science and Technology Substitution Method. Result from the activities were: 1) Aquaponic system socialization activities on catfish enlargement can increase members' understanding of the aquaponic system in increasing family income; 2) Aquaponic system preparation training activities can increase knowledge about aquaponic techniques in creating double income; 3) Aquaponic system practice activities can encourage the independence of the members in developing vegetable growing places as additional income; 4) Assistance activities can provide moral assistance and assist group members in finding solutions to various operational and marketing management constraints; and 5) Community service activities on group aquaponic have an impact on additional revenue from the vegetable crop sales sector, although it is relatively small.Keywords: Double Income, catfish waste, aquaponic, production management.ABSTRAKPermasalahan mitra pada kegiatan pengabdian diantaranya: kurangnya sosialisasi sistem akuaponik, kurangnya pengetahuan sistem akuaponik dalam menciptakan double income, belum memahami implementasi sistem akuaponik, tidak adanya pendampingan dalam mencari solusi atas masalah, dan apa dampak dari kegiatan pengabdian terhadap peningkatan pendapatan keluarga. Tujuan pengabdian adalah untuk membantu mencari solusi dalam menyelesaikan permasalahan yang dihadapi kelompok usaha budidaya pembesaran ikan lele terutama berkaitan dengan peningkatan pendapatan ekonomi masyarakat melalui manajemen produksi sistem akuaponik sederhana. Solusi yang diberikan adalah dengan memperkenalkan manajemen produksi mutualisme yaitu mengolah air kolam pembesaran ikan lele untuk dijadikan pupuk cair sebagai nutrisi sayuran dengan sistem akuaponik. Targetnya agar dapat meningkatkan ekonomi (valued added) melalui pemanfaatan sumber daya yang ada seperti limbah kotoran lele sebagai usaha tambahan dengan harapan mereka dapat menambah unit usaha guna meningkatan pendapatannnya selain dari usaha inti pembesaran ikan lele. Metode yang digunakan adalah melalui pelatihan dan metode substitusi Ipteks. Hasil dari pengabdian ini adalah: 1) Kegiatan sosialisasi sistem akuaponik pada pembesaran ikan lele dapat meningkatkan pemahaman para anggota terhadap kelebihan dari sistem akuaponik dalam menambah penghasilan keluarga; 2) Kegiatan pelatihan penyusunan sistem akuaponik dapat meningkatkan pengetahuan tentang teknik akuaponik dalam menciptakan double income; 3) Kegiatan praktek sistem akuaponik dapat mendorong kemandirian para anggota dalam mengembangkan tempat tanam sayuran sebagai tambahan pendapatan; 4) Kegiatan pendampingan dapat memberikan bantuan moril dan membantu para anggota kelompok dalam mencari solusi terhadap berbagai kendala manajemen operasional maupun manajemen pemasaran, dan 5) Kegiatan pengabdian tentang sistem akuaponik pada anggota kelompok memberikan dampak terhadap penambahan pendapatan dari sektor penjualan tanaman sayuran walaupun relatif kecil.Kata kunci: Double income, limbah ikan lele, akuaponik, manajemen produksi.